Preliminary inventory of fruit fly species (Diptera, Tephritidae) in mango orchards in the Niayes region, Senegal, in 2004 - Vayssières, Jean-François; Vannière, H.; Gueye, P.S.; Barry, O.; Hanne, A.M.; Korie, S.; Niassy, A.; N'Diaye, M.; Delhove, G.E. (EDP Sciences, 2011)
Introduction. Knowledge of tephritid diversity in Senegal was poor before 2004, so PIP-COLEACP and CIRAD, in collaboration with Cérès-DPV, carried out, in 2004, trapping for preliminary detection of fruit flies in six orchards in the Niayes zone. Materials and methods. We selected three mixed mango orchards and three homogeneous mango orchards in this zone. In each orchard, we used three attractants: Terpinyl acetate (Ter), Trimedlure (Tri) and Torula (Tor). Traps were serviced weekly. Results. We captured 77 642 fruit flies in more than 4 months including mango season; they were represented by 18 identified fly species, including ten Ceratitis, six Dacus and two Bactrocera species. Two very serious pests were identified with the confirmation of Bactrocera cucurbitae (Coquillett) for cucurbit crops and the detection of B. invadens Drew Tsuruta & White for fruit crops. The two most abundant species of Ceratitis were C. cosyra and C. silvestrii. Discussion. We captured more fruit fly species in mixed mango orchards than in homogeneous mango orchards. Bactrocera invadens was also more abundant in mixed orchards, probably because of its polyphagous status. This new invasive species, B. invadens, can have many hosts in mixed mango orchards, enhancing its breeding potential. Conclusion. Effective management to deal with this alien species requires: (i) improvement of basic and applied research; (ii) an effective IPM package; (iii) an area-wide management approach; (iv) a sub-regional effort on the part of researchers, extension services, growers, exporters, farming associations and the different actors in fruit value chains (mainly mango).